It's Fun To Overcome Learning Loss At Sd Negeri 16 Banda Aceh - Sarniyati Yusmanita, S.Pd., M.Pd (Cita konsultindo, 2022)
This Best Practice was carried out to find out whether the implementation of assistance to teachers in applying reverse learning can restore learning after learning loss occurs at SD Negeri 16 Banda Aceh. Effectively the application of the assistance method is carried out for class teachers and subject teachers in their own schools for the following reasons: 1) The teacher is the main actor in learning activities, 2) Allows writers to provide ongoing guidance and assistance, 3) Easy to coordinate. Implementation of best practices that are carried out to facilitate the resolution of learning loss problems in schools, the authors need to provide assistance to 18 teachers as the main actors of learning activities in schools. 1) the implementation of assistance to teachers in implementing reverse learning at SD Negeri 16 Banda Aceh has been able to develop teacher competence in designing digital media in the form of classroom learning videos. 2) The application of teacher assistance by applying reverse learning to teachers is seen as effective in learning recovery after learning loss occurs in students at SD Negeri 16 Banda Aceh. 3) parents of students are actively involved in learning the reverse learning model applied in schools. 4) students are trained to study independently at home. The results obtained from the impact of the assistance activities have increased the quality of learning with marked student achievements that won city and national level champions.